Evaluasi Kinerja Mesin Bending Hidrolik Menggunakan Metode Overall Equipment Effectiveness (OEE), Failure Mode and Effect Analysis (FMEA), dan Fault Tree Analysis (FTA) - Khasanah, Rahayu; Susilawati, Indri; Sodikin, Imam (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2023)
PT Hari Mukti Teknik is a company engaged in the Manufacturing Industry that produces laundry machines and other mechanical engineering. The problem that occurs in the production process at PT Hari Mukti Teknik is the performance of the bending machine which has a high downtime value of an average of 994 minutes per month. The purpose of this study is to evaluate the performance of the bending machine by knowing the level of effectiveness of the performance of the bending machine using the OEE method, knowing the causes of losses that affect the level of effectiveness of machine performance, using the six big losses method and analyzing losses using the Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methods to propose improvement efforts. Based on the results of data processing, the average Overall Equipment Effectiveness (OEE) value of bending machines in one year is 84.21%, with the largest losses being equipment failure losses of 7.34%. Proposed improvements based on FMEA and FTA analysis are to carry out periodic maintenance, make a predictive maintenance list, carry out periodic re-checks, carry out periodic lubrication, check environmental cleanliness, and replace damaged components.